RESILIENCE OF A TEACHER OF A HIGHER EDUCATION INSTITUTION UNDER THE CONDITIONS OF THE MARTIAL STATE - Balakhtar, Kateryna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The relevance of the study is determined by the need to build the resilience of a teacher of a higher education institution under martial law as the ability to resist stress and show mental stability under martial law in the process of implementing professional activities aimed at forming key competencies of future specialists under the requirements of international institutions. The purpose of the article is to study the resilience of teachers of higher education institutions in the conditions of martial law. The essence of the "resiliency" phenomenon is revealed as a complex, multidimensional and inherently dynamic complex of human characteristics; the individual's ability to resist and adapt to adverse and traumatic events. Resilience is highlighted as the ability to withstand damage, swift recover and successfully adapt to adverse circumstances. Resilience is considered in three dimensions - as a trait or the ability of an individual to overcome stress, as a coping process and as an adaptive protective mechanism of an individual that allows one to resist stress or adapt after psychological trauma. The advantages of the action of resilience are determined: high adaptability, psychological well-being and success in the activities of teachers of higher education institutions and the main features of resilient people (social features, emotional features, cognitive/academic features). The components of teachers' resilience (hope, optimism, adaptability, stability) are highlighted. The psychological factors and features of the development of resilience of teachers of higher education institutions are substantiated (purposefulness, directing life towards a specific goal, the ability to plan activities, motivation for success, a sense of coherence between life and professional activity, the preference for positive emotions, resilience, optimism, high spirituality of the individual, etc.